Reliability Analysis of Regular Multistage Interconnection Networks - Baloda, Sushila (My University, 2010)
The performance of a computer system depends directly on the time required to perform a basic operation and the number of these basic operations that can be performed concurrently. High performance computing systems can be designed using parallel processing. Parallel processing is achieved by using more than one processors or computers together they communicate with each other to solve a given problem. MINs provide better way for the communication between different processors or memory modules with less complexity, fast communication, good fault tolerance, high reliability and low cost. Reliability of a system is the probability that it will successfully perform its intended operations for a given time under stated operating conditions. In this thesis an important issue in the design of MINs is the provision of more than one path between each input-output pair. There are mainly three types of reliability measures, which are important to MINs, namely terminal reliability, broadcast reliability and network reliability. The purpose of this thesis is to develop tighter bounds for network reliability for the extra-stage MIN. In this thesis Reliability analysis of three regular multistage interconnection networks namely SEN, Omega and Cube has been done. With the addition of one and two extra stages more regular MINs namely SEN+, Omega+, Cube+ and SEN+2, Omega+2, Cube+2 are derived from SEN, Omega and Cube respectively. As measures of network performance, the terminal, broadcast and network reliability of all three networks have been evaluated. From the reliability analysis following conclusions have been made. Addition of one stage to any of SEN, Omega or Cube networks provide higher reliability in terms of terminal, broadcast and network, than the addition of two stages in the corresponding network. Further comparative analysis among SEN+, Cube+ and Omega+ has shown that Cube+ is most reliable than SEN+ and Omega+.
M.E. (CSED)
Keywords: Reliability, Multistage Interconnection Networks, SEN, Omega, CUBE